An Analysis of Borrowing Technique Used in The Novel “A Study in Scarlet” by Arthur Conan Doyle - Nahdoh, Wardhatun; Supatmiwati, Diah; Syamsurrijal, Syamsurrijal (Humanitatis : Journal of Language and Literature, 2025)
Literary translation plays a crucial role not only as a linguistic bridge but also as a medium for transferring culture, aesthetic values, and complex emotional expressions. Unlike technical or legal translation, literary translation demands greater cultural and linguistic sensitivity, especially when dealing with culture-specific terms. One translation technique frequently employed in this context is borrowing, which helps preserve cultural authenticity in the target language. In Arthur Conan Doyle’s classic detective novel A Study in Scarlet, borrowing is particularly significant because the novel introduces cultural, social, and historical elements of 19th-century England, reflected in its distinctive vocabulary and cultural references. The objective of this research is to identify the borrowing technique used in the novel “A Study in Scarlet”, translated into “Penelusuran Benang Merah”. This study employed a descriptive qualitative method to describe the borrowing techniques found in the text. The analysis is based on Molina and Albir’s (2002) framework for translation techniques and Newmark’s (1988) classification of foreign cultural terms into five domains. The findings reveal 70 borrowing instances, comprising 49 pure borrowings and 21 naturalized borrowings, distributed across material culture, social culture, gestures and habits, organizations, and abstract concepts. These results highlight how borrowing functions as a translation strategy that simultaneously preserves cultural authenticity and ensures the readability of the target text.